Liquid bread : beer and brewing in cross-cultural perspective - Schiefenhövel, Wulf, 1943-; Macbeth, Helen M. (Anthropology of food and nutrition, 2011)
"Beer is an ancient alcoholic drink which, although produced through a more complex process than wine, was developed by a wide range of cultures to become internationally popular. This book is the first multidisciplinary, cross-cultural collection about beer. It explores the brewing processes used in antiquity and in traditional societies; the social and symbolic roles of beer-drinking; the beliefs and activities associated with it; the health-promoting effects as well as the health-damaging risks; and analyses the modern role of large multinational companies, which own many of the breweries, and the marketing techniques that they employ."--